Survey of studies of stigmatization and discrimination of patients with HIV/AIDS by medical personnel – comparison of Polish experience with the global situation - Rogala, Maciej; Mach, Tomasz; Motyka, Marek; Donesch-Jeżo, Ewa (Journal of Stomatology, 2015)
Introduction. Since the emergence of the problem of HIV/AIDS infection, its pejorative social perception has been observed. The results of studies indicate occurrence of stigmatization and discrimination of patients with diagnosed HIV/AIDS by medical personnel, including doctors and dentists. Aim of the study. To review the literature pertaining to the findings of studies of stigmatization and discrimination of patients with HIV/AIDS in Poland and abroad. Material and methods. The studies were carried out with the use of the search Engine Medline/PubMed taking into account the experience in this area in Poland. The survey of the literature was supplemented with other articles by Polish and foreign authors, as well as the reports of international projects. The following keywords were used: “stigmatization and discrimination of patients with HIV/AIDS”, “stigmatization and discrimination by medical staff/doctors”, “relationships between doctors and patients with HIV/AIDS”, “stigmatization of HIV/ AIDS”, “discrimination of HIV/AIDS.” Results and discussion. The previous studies of these phenomena reveal that both in Poland and in other countries the cases of stigmatization and discrimination of patients with HIV/AIDS by doctors and dentists do occur, and medical personnel is at the forefront of the groups stigmatizing and discriminating against the infected patients. The repeated manifestations of these phenomena include: refusal of medical and dental help, refusal of carrying out an examination/ procedure, or admitting to a hospital ward. The results of some investigations and presented theoretical concepts suggest that among underlying causes of these negative behaviours and attitudes towards these patients may be the feeling of fear or anxiety, as well as the lack of decent knowledge of the ways of viral transmission. Summary. The presented results of the research into the problem of stigmatization and discrimination by medical personnel focus mainly on the description of their manifestations towards patients with HIV/AIDS. Only some of these studies, within a narrow scope, try to depict the causes of these negative behaviours and attitudes. There are no studies, especially in Poland, thoroughly illustrating this problem. Therefore, it seems justified to undertake research analysing deeply the area of the relationship between medical personnel and patients in order to understand better the aetiology of stigmatization and discrimination, and as a result, to eliminate such cases in health care.